2017
DOI: 10.1371/journal.pone.0184576
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of pretreatment serum levels of VEGF and its receptors, IL- 8, and their prognostic value in type I and II endometrial cancer patients

Abstract: ObjectivesThe study aimed to assess the usefulness of the determination of cytokines: IL-8, VEGF and its soluble receptors: VEGF-R1, VEGF-R2 in patients with endometrial cancer (EC).Material/MethodsThe study group consisted of 118 patients with EC subjected to surgical treatment. Before the treatment we determined the serum levels of cytokines IL-8, and VEGF as well as VEGFR1 and VEGFR2 receptors. For comparison, the concentration of CA 125 was also measured. VEGFR1 and CA 125 were determined in the COBAS e601… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 25 publications
(24 reference statements)
2
23
1
1
Order By: Relevance
“…This discrepancy might be related to different concentrations obtained in healthy controls group. In oppose to our findings were results obtained by Kotowicz et al [27], where concentrations of VEGF-A and VEGFR-2 were not statistically significant, but their work concerned different type of tumor (endometrial cancer).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This discrepancy might be related to different concentrations obtained in healthy controls group. In oppose to our findings were results obtained by Kotowicz et al [27], where concentrations of VEGF-A and VEGFR-2 were not statistically significant, but their work concerned different type of tumor (endometrial cancer).…”
Section: Discussioncontrasting
confidence: 99%
“…Statistically significant plasma over expression and high gene expression of VEGF-A, VEGF-C, VEGF-D and VEGFR-2 have been detected in patients suffering from many types of tumors, also breast cancer [6, 9, 23–27]. We have demonstrated statistically significantly higher plasma concentrations of almost all tested parameters when compared to control groups.…”
Section: Discussionmentioning
confidence: 53%
“…Due to the sustained action of VEGF, a large number of new blood vessels can be produced in the progression of endometrial cancer. The new blood vessels not only provide the tumor tissue with the nutrients necessary for growth, but they also remove metabolic products [50,51]. As a major regulator of neovascularization in endometrial cancer, HIF-1 directly regulates the expression of VEGF at the gene level.…”
Section: Signaling Pathways In Endometrial Carcinogenesismentioning
confidence: 99%
“…Interesting observations are also provided by studies on a group of 118 patients with endometrial cancer carried out by Kotowicz et al , in which they analyzed the expression profile of VEGF-A, VEGFR-1, VEGFR-2 and IL-8. They emphasize the clinical value of IL-8 and VEGFR-2 as potential prognostic factors and that increased VEGF-A activity may be useful in pre-operative assessment of para-aortic lymph node status [ 33 ]. Mathur et al observed elevated serum level of VEGF-B in early, advanced and persistent cervical cancer, as well as in ovarian and endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%